2016
DOI: 10.1021/acsphotonics.6b00087
|View full text |Cite
|
Sign up to set email alerts
|

Circular Differential Two-Photon Luminescence from Helically Arranged Plasmonic Nanoparticles

Abstract: We report the observation of a circular differential two-photon photoluminescence (TPPL) response from a three-dimensional chiral metamaterial, comprising a system of achiral (spherical) metal nanoparticles arranged on a chiral (helical) dielectric template. The enhanced dipolar response of the individual particles arising from their strong electromagnetic coupling resulted in strong photoluminescence under peak illumination intensities as low as 2 × 103 W/cm2. The TPPL signal was of approximately equal magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Embedding the QDs into the metamaterial host enhanced the TPL‐CD of the local QD emitters. The observation of TPL‐CD was also reported from silver nanoparticles arranged in a chiral fashion on a dielectric helical template . Third harmonic generation circular difference (THG‐CD) effects have recently been demonstrated in a chiral metamaterial covered with organic conjugated polymer (PFO) .…”
Section: Nonlinear Chiropticsmentioning
confidence: 77%
See 1 more Smart Citation
“…Embedding the QDs into the metamaterial host enhanced the TPL‐CD of the local QD emitters. The observation of TPL‐CD was also reported from silver nanoparticles arranged in a chiral fashion on a dielectric helical template . Third harmonic generation circular difference (THG‐CD) effects have recently been demonstrated in a chiral metamaterial covered with organic conjugated polymer (PFO) .…”
Section: Nonlinear Chiropticsmentioning
confidence: 77%
“…It was found that the strength of the chiroptical interaction increases almost exponentially as the nanoparticles where brought closer together, which also caused a shift and a broadening of the CD spectrum. Two‐photon‐induced photo‐luminescence CD was also reported from this kind of systems …”
Section: Design Of Chiral Materialsmentioning
confidence: 80%
“…Nonlinear optical forms of response represent a further tier of opportunities. Distinctive features have relatively recently been shown to arise with two-photon absorption in experiments on a variety of chiral organic systems [109][110][111][112][113][114], for which the corresponding CD was first predicted by theory many years ago [115][116][117] and twophoton circular differential luminescence has indeed now been observed in helically arranged plasmonic nanoparticles [118]. As Friese leads the way in predicting a threephoton analogue of CD [119], it seems likely that proof of a CPL counterpart may also not be far away.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of 3D‐resolved two‐photon‐actuated nanomedicine has been exploited via various nanomaterials such as semiconductor and carbon nanodots, polymeric, organic, silicon, gold, graphene and graphene oxide, silica hybrid, and other inorganic nanomaterials. What are the advantages of silica‐based nanoparticles?…”
Section: Two‐photon‐sensitive Organosilica Nanomaterialsmentioning
confidence: 99%